Prevalence and predictors of heated tobacco products use among male ever smokers: results from a Korean longitudinal study - Jeeeun Yi; Cheol Min Lee; Seung-sik Hwang; Sung-il Cho (BMC, 2021)
Abstract Background This study examined sociodemographic and tobacco-related factors of heated tobacco products (HTPs) use among adult ever smokers in South Korea where the sales of HTPs have been rapidly increasing since their launch in June 2017. Methods Before the launch of HTPs in Korea, participants comprised male ever smokers (234 current smokers and 37 quitters) who participated in the Korea National Health and Nutrition Examination Survey from 2015 to 2017 through one-to-one interview survey and agreed to participate in the follow-up surveys through telephone in December 2017. Data were analyzed using logistic regression, to explore sociodemographic and smoking behavior-related factors of HTPs use. Results Overall, 10.7% (29/271) of participants responded to using HTPs and 8.1% (22/271) were current HTPs users at the time of the follow-up survey. Multivariate analysis showed that HTPs use is associated with middle age (36 to 49 years old) (aOR = 3.72, CI = 1.16-12.0) (vs. ≥ 50 years), higher income (4Q vs 1Q: aOR = 2.71, CI = 1.16-6.34), and higher educational level (college or higher: aOR = 2.40, CI = 0.87-6.60). Also, vaping experience at baseline was highly associated with HTPs use (aOR = 3.11, CI = 1.22-7.93 for the former experience; aOR = 9.14, CI = 2.34-35.6 for current). However, smoking amount and level of motivation for smoking cessation were not found to be predictors of future HTPs use when limited to current smokers at baseline. Conclusions The results showed that vaping experience regardless of current smoking behavior and higher socioeconomic status were found to be associated with subsequent HTPs use among ever smokers. Further studies are required to explore whether this association is causal.